Sutan sjahrir socio-democratic ideas reviewed from the perspective of jurgen habermas political philosophy - Setiawan, Mugig; Eka Putra, Surya Desismansyah (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Prime Minister Sutan Sjahrir's political policies promoted progressive social democratic values. The concept of social democracy is not merely a mechanical combination of socialism and democracy. Instead, it views the two as two sides of the same coin that complement and reinforce each other. This research examines Sutan Sjahrir's socio-democratic ideas, which are analyzed using JÃ¼rgen Habermas's political philosophy theory. The aim is to identify the socio-democratic ideas promoted by Sutan Sjahrir, which will be reviewed from the perspective of JÃ¼rgen Habermas's political philosophy. This study employs a literature review method, which is analyzed using content analysis. This method is used to collect and analyze the content of a text, including elements such as words, image meanings, symbols, ideas, themes, and various forms of messages that can be conveyed. The results of this research show (1) Sutan Sjahrir's socio-democratic ideas regarding the separation of powers, social democracy, true independence, equality, and social justice. (2) Sutan Sjahrir's socio-democratic ideas on the separation of powers, social democracy, true independence, equality, and social justice are relevant to Habermas' ideas on the public sphere and deliberative democracy, which emphasize active citizen participation in political decision-making